GAMBARAN PENGETAHUAN IBU TENTANG PENGGUNAAN MEDIA SOSIAL PADA ANAK USIA SEKOLAH DI SD SWASTASANTA LUSIA SEI ROTAN MEDAN TAHUN 2019 - Desriati Sinaga; Susi Santi Lumban Gaol (STIKes Santa Elisabeth Medan, 2020)
Introduction: Knowledge forms one's actions or results from knowing and occurs after people sense a certain object. From experience, it is known that behavior based on knowledge will last longer than behavior that is not based on knowledge. The factors underlying the mother's knowledge are education, occupation and age. The negative impact of the use of social media on school-age children is reduced communication with parents, weak psychomotor abilities to draw, reduced singing and playing, difficulty adapting to subject matter and difficulties in socializing with the environment. This study aims to determine the description of mother's knowledge about the use of social media in school-age children at SD Santa Lusia Sei Rotan Medan in 2019Method: The method used in this research is descriptive design and the sample in this study is mothers who have as many as six grade school-age children at SD. 42 people with total sampling technique. The instrument used in this study was a questionnaire.Result: The results showed that the knowledge of mothers about the use of social media in school-aged children at SD Santa Lusia Sei Rotan Medan in 2019 was more knowledgeable (53.1%).Duscussion: Mothers are expected to know new information and time limits on the use of social media that have a positive impact on children, such as providing educational videos, learning languages and opening social media for children's content.